Smart Regulation As A New Approach In Regulatory Reform In Indonesia - Uz Zaman, Muhamad Nafi (Jurnal Rechts Vinding: Media Pembinaan Hukum Nasional, 2024)
The regulatory reform hasn’t yet effective results. Because the strategy is still pragmatic and hasn’t addressed root of the problem. Through a conceptual study, it is found that regulatory arrangements in Indonesia still use a centralistic approach, where the government becomes the main subject of regulation and places state regulation as the only instrument. Meanwhile, the smart regulation approach emphasizes the combination of regulatory instruments that not only focus on the centralization of authority in the government but also decentralize it to other non-governmental subjects. The goal is to produce efficient, agile, and egalitarian regulations. The implementation is starting from promoting regulatory decentralization, determining the priority scale for regulatory formation, and establishing a scheme for combining various regulatory instruments